Analisis Penetapan Harga Pokok dengan Metode Activity Base Costing pada Produk Bakery and Cake - Muhammad Fahmi Affandi; Yetti Meuthia Hasibuan; Nismah Panjaitan (Universitas Harapan Medan, 2021)
The research conducted is the analysis of the costing of goods based on the method of activity based costing (ABC) to determine the cost of making a cake and determine the selling price per one cake product. So far, Bakery and Cake Shop in determining the cost of products using conventional methods, and based on the results. Research and discussion carried out at the Bakery and Cake Shop can be seen that the manufacturing costs and selling price per product have quite high advantages such as brownie cake with a manufacturing cost of IDR 32,047 and a selling price of IDR 60,000 with a profit margin of 47%, banana cake with a manufacturing cost of IDR 31,381 and a selling price of IDR 55,000 with a profit margin of 43%, Mocca rolls with a manufacturing cost of IDR 26,586 and a selling price of IDR 45,000 with a profit margin of 41%, olu Chocolate Rolls with a manufacturing cost of IDR 23,016 and a selling price of Rp. 40,000 with a minimum margin with 42%, Rollbery Rolls with a manufacturing cost of IDR 26,916 and a selling price of IDR 45,000 with a profit margin of 40%, cheese rolls with a manufacturing cost of IDR 30,916 and a selling price of IDR 55,000 with a profit margin of 44%, and pandan cake with a manufacturing cost of Rp. 25,626 and a selling price of Rp. 45,000 with a profit margin of 43%, it can be concluded that an accurate calculation of the cost of production can be done using the Activity Based Costing (ABC) method.